HP0013 Changes in measures of pain and function in intervention studies of severe knee osteoarthritis: comparison to patient perceptions. (1st June 2001) - Lamb, SE; Toye, F; Barker, KL; Barrington, S
Abstract : Background: Questionnaires and physical performance tests are recommended for measuring changes in pain and function in knee osteoarthritis. The significance of changes in these measures is poorly understood. Aim: To compare associations between patients' perceptions of change in function and pain due to a chronic disease management program, with physical performance tests and questionnaire assessments. Method: The sample were 109 people being considered or waiting for knee replacement, who attended a six-week chronic disease management program. Interventions were goal setting, planning, symptom management, exercise, diet and lifestyle advice. Function and pain were assessed before and after the program by a physiotherapist, using the WOMAC, 1 Arthritis self-efficacy scale, 2 visual analogue scales (VAS) of distress and pain, timed measures of walking and sit-to-stand, and leg extensor power (LEP, Watts/Kg). 3 Patients gave a global assessment of change in pain and function as a result of the program as (1) much worse (2) somewhat worse (3) same (4) somewhat better (5) much better. Less than 5% of patients reported worsening symptoms, therefore categories 1–3 were combined. The mean change in outcome measures was calculated for the three levels of global patient assessments. A non-parametric ANOVA was used to test for statistically significant differences in outcomes across the three levels of global assessment, and included a test for linearity. Results: The mean age of participants was 69 (SD 8.5), 44% were male, median duration of symptoms was 6 yrs (range 57.5). Over 70% of patients reported being somewhat or much better in function or pain after the program. Global ratings of pain and function demonstrated strong, linear associations with changes in WOMAC function, LEP and self-efficacy (shown for pain in the Table 1 ). Improvements in pain were associated with the baseline WOMAC pain score. Age, sex, and severity of disease were not associated with patients' global assessments. Neither were changes in walking speed, sit-to-stand, VAS distress, VAS pain or WOMAC pain scores. Conclusion: The results suggest possible minimum clinically significant differences for use in clinical trials, and measures that reflect patient perceptions of the benefits of a chronic disease management program. References: Bellamy, et al . 1988;15(12)1833–40 Barlow JH, et al . Psych Health Med. 1997;2(1):3–17 Bassey, et al . Eur J Appl Physiol. 1990;60(5):385–90